2009
DOI: 10.1016/j.pmrj.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Capsulitis: A New Management Protocol to Improve Passive Range of Motion

Abstract: This study suggests that this adhesive capsulitis management protocol is effective and produces a significant improvement in the passive range of motion immediately after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Only eight studies in this review reported an image-guided injection technique that ensured intra-articular placement of all corticosteroid injections - five used fluoroscopy and three used ultrasound 17,18,32,36,38,40,41,44 . Studies have shown low accuracy of glenohumeral injections performed without image guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Only eight studies in this review reported an image-guided injection technique that ensured intra-articular placement of all corticosteroid injections - five used fluoroscopy and three used ultrasound 17,18,32,36,38,40,41,44 . Studies have shown low accuracy of glenohumeral injections performed without image guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvement in shoulder function, the authors were unable to say which fraction of the protocol was most effective. 21 Shanahan et al carried out SSNB without the aid of a nerve stimulator or imaging techniques, as in our study, but used 1 mL of 40 mg methylprednisolone, associated with bupivacaine 0.5%. 22 Neither Mitra nor Shanahan assessed QoL as the outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Barbotage 58 Repeated injection and aspiration of fluid to break up and remove calcification, usually within a tendon Brisement [59][60][61] The injection of fluid into the space between a tendon and its paratenon or sheath; brisement has also been used to refer to injection of saline or other fluid into a joint to break down adhesions (eg, in treatment of adhesive capsulitis).…”
Section: Aspirationmentioning
confidence: 99%